Perception of Preschool Children about Environmental Pollution - Meltem Duran (Journal of Education in Science, Environment and Health)
The purpose of this study is to determine the perceptions of preschool children on environmental pollution. A qualitative research method was employed in the current research. The data of the study were collected by semi-structured interview and drawing techniques and the obtained data were analyzed with a descriptive analysis method. The sample consisted of 67 children between 3 and 6 years of age, attending the kindergarten of different schools located in Giresun city center. It was observed that the 3-year-old group emphasized germs and 4 and 6-year old groups emphasized air and sea pollution. When asked about the prevention of environmental pollution, the younger age groups generally stated as "we should throw the garbage into the trashcan", and the group of 6-year-olds stated as "we should not cut the trees". In terms of information sources, the 3-year-old group usually stated their mother, while the groups of 4, 5, and 6-year-olds stated both their mothers and fathers. The children had difficulty in expressing the factors that cause air pollution verbally in the interviews, but in their drawings, they were able to reveal their air pollution perceptions more easily and concretely.